Post‐induction infliximab trough levels and disease activity in the clinical evolution of pediatric ulcerative colitis. Issue 4 (1st May 2020) - Moore, Hillary; Dolce, Pasquale; Devas, Nina; Baldassano, Robert; Martinelli, Massimo
Abstract : Background and aims: Recent adult evidence suggests that infliximab (IFX) trough levels (TL) in patients with severe ulcerative colitis (UC) may be decreased. The aims of our study were to compare post‐induction IFX TL of children with severe versus moderate UC and to evaluate short‐ and long‐term outcomes. Methods: In this single‐center retrospective study, children with a diagnosis of UC starting IFX with a Pediatric Ulcerative Colitis Activity Index (PUCAI) ≥35 and with available post‐induction TL were recruited. UC characteristics, IFX dosage and interval, primary non‐response, IFX failure, and surgery after 24 months were collected. Post induction TL, anti‐IFX antibodies, and laboratory evaluations at the time of starting IFX were also acquired. Results: A total of 90 children were enrolled, of whom 39 (43.3%) were classified as severe UC and 51 (56.6%) as moderate UC. Median post‐induction IFX TL were lower in severe UC versus moderate group (5.5 vs 10.3; p = 0.03), despite a more frequently intensified IFX regimen. Children in the higher TL quartiles showed increased rates of clinical, biological, and combined remission ( p = 0.04, p < 0.001, and p = 0.01, respectively). In a multivariate analysis, a PUCAI ≥65 and time interval from last IFX infusion were the only predictors associated with IFX TL. At 24 months, children in the higher TL quartiles had a decreased risk of IFX failure ( p = 0.002). The severe UC group showed a higher risk of IFX failure at 24 months (16/23 (41%) vs. 11/40 (21.6%); p = 0.05). Kaplan–Meier methods demonstrated a trend toward statistical significance, with a two‐year cumulative colectomy rate of 15.38% (95% confidence interval (CI) 8.1–15.6%) in children with severe UC and 3.92% (95% CI 2.9–10.8%) in patients with moderate UC (logrank test p = 0.06). Conclusions: Children starting IFX with severe UC showed lower post‐induction TL and poor disease outcomes. Achieving adequate TL was associated with better efficacy outcomes.